Clonal haematopoiesis harbouring AML-associated mutations is ubiquitous in healthy adults - Andrew L. Young (Nature Portfolio, 2016)
Clonal haematopoiesis has been thought to occur in less than 10% of individuals younger than 70 years old. Here, the authors use an error corrected next-generation sequencing method to find clonal haematopoiesis in the peripheral blood of 19 of 20 healthy 50–70 year old individuals.